Factors influencing pain intensity during topical photodynamic therapy of complete cosmetic units for actinic keratoses - Gholam, Patrick; Denk, Katharina; Weberschock, Tanja; Enk, Alexander; Hartmann, Martin (Journal of the American Academy of Dermatology, 2010)
Background - Topical photodynamic therapy is a good treatment option for extensively photodamaged skin with multiple actinic keratoses. Pain is one of the major adverse effects during and after the treatment. - Objective - We sought to determine the pain intensity and its influencing factors during the extensive photodynamic treatment of complete cosmetic units. - Methods - In total, 104 patients with 411 treated fields were enrolled in this retrospective monocentric study. All patients had multiple actinic keratoses on the face, scalp, or back of hands and received an extensive treatment of the complete photodamaged area in our dermatologic outpatient department between February and May 2009. Pain was rated using a visual analog scale directly and 8 hours after photodynamic therapy. - Results - Multifactorial analysis of the data shows that pain intensity is dependent on sex of the patient (P = .030) and location of the treated field (P < .001). Visual analog scale scores were independent of the age and skin type of the patient. No significant difference in pain between the use of 5-amino-4-oxo-pentanoate (methylaminolevulinate) and 5-aminolevulinic acid was noticed. During treatment, mean visual analog scale scores ± SEM of the different locations were 2.5 ± 0.36 (hand), 3.6 ± 0.35 (occiput), 5.2 ± 0.19 (forehead), 5.9 ± 0.20 (cheeks), and 7.4 ± 0.48 (lips). Eight hours after treatment the mean pain ± SEM in all locations was reduced significantly (P < .001) from 5.2 ± 0.14 to 3.0 ± 0.14. The rate of therapy interruptions showed a significant correlation (P = .044) with the location of the treated field. In all, 71% of the patients showed a good and 29% a poor clinical outcome. - Limitations - Because of the retrospective study design not all factors that may influence pain (eg, protoporphyrin IX fluorescence) were recorded. - Conclusion - These results show that pain intensity is dependent on the location of the treated field. Pain intensity is higher in male patients. After 8 hours pain decreases significantly.